algebraic transformation: y = x^3-3x shifted along x-axis by

steveo

New member
Joined
Mar 29, 2009
Messages
2
I am having understanding how to do a transformation of the following equation, shifting it along the x-axis by 4 units.
y=x^3-3x
Please help me understand the process
 
Re: algebraic transformation

Get out your graph paper or your graphing calculator.

Graph your original equation y=x[sup:unj69499]3[/sup:unj69499]-3x

Then graph y=(x-4)[sup:unj69499]3[/sup:unj69499]-3(x-4) and see what happens.
 
Re: algebraic transformation

Thanks. I tried this before but must have made repeated entry errors. The solution: y=(x-4)^3-3(x-4) is correct.
 
Top